Beyond tuberculosis: A rare case of neuromelioidosis (Indian Journal of Case Reports, 2026)
Melioidosis is an emerging infectious disease in India caused by Burkholderia pseudomallei, with central nervous system (CNS) involvement being particularly rare and associated with high mortality. Neuromelioidosis often mimics tuberculosis, malignancy, or other granulomatous infections, leading to delayed diagnosis and treatment, especially in non-coastal regions. We report a case of a 44-year-old male from Rajasthan with a 4-year history of type 2 diabetes mellitus who presented with prolonged fever, headache, irritability, and focal neurological deficits. Neuroimaging revealed multiple right temporo-occipital T2 hyperintense lesions with hemorrhagic changes initially misinterpreted as tubercular granulomas. Cerebrospinal fluid analysis demonstrated clear fluid with five lymphocytes/mm3, protein 82 mg/dL, glucose 72 mg/dL, and sterile culture. Microbiological work-up for tuberculosis and commontropical infections was negative. Blood culture subsequently grew B. pseudomallei, establishing the diagnosis of Neuromelioidosis. The patient was treated with intravenous meropenem followed by oral cotrimoxazole, resulting in clinical and radiological improvement, though residual neurological deficits persisted. Neuromelioidosis should be considered in diabetic patients presenting with unexplained CNS lesions, even in non-endemic or arid regions, such as Rajasthan. This case highlights the expanding geographical footprint of melioidosis in India and underscores the need for heightened clinical suspicion, early microbiological diagnosis, and appropriate prolonged therapy to reduce morbidity and mortality.